Fast repetitive response as a useful predictor of long-term success of radiofrequency ablation of right ventricular outflow tract ventricular tachycardia: Hitri repetitivni odgovor kot uporaben napovedni dejavnik dolgoročne uspešnosti po radiofrekvenčni ablaciji ventrikularne tahikardije iz iztočnega trakta desnega prekata - Vokac, Damijan; Nedog, Viljemka; Kanic, Vojko; Naji, Franjo (Acta Medico-Biotechnica, 2021)
Purpuse: Idiopathic right ventricular outflow tract ventricular tachycardia (RVOT-VT) is the most frequent type of ventricular arrhythmia in patients without structural heart disease and is frequently treated using radiofrequency ablation (RFA). Fast non-sustained ventricular arrhythmia showing the same morphology as initial arrhythmia, the so-called fast repetitive response (FRR), is sometimes observed during ablation of the desired region. In this study, we evaluated the prognostic impact of FRR in patients after successful RFA of RVOT- VT.Methods: A prospective observational case-control design was selected for the study. We included patients with successful RFA of previously registered RVOT- VT. Patients with provoked FRR during RFA were assigned to the FRR group and 33 patients displaying no FRR to the control group. Overall, 33 patients in both groups were monitored for the subsequent 24 months. Parameters of the procedure, such as duration, energy application as well as long-term success, were compared between the two groups.Results: We observed significantly shorter duration of procedure performance (120±29 min vs. 70±16 min; P
Keywords: radiofrequency ablation; right ventricular outflow tract ventricular tachycardia; fast repetitive response